Impact of kelp and fucoidan on lipid metabolism in large yellow croaker (Larimichthys crocea) - Sifeng Zhu; Chengwei Huang; Bin Du; Rui Yang; Qijun Luo; Haimin Chen; Juanjuan Chen (Aquaculture Reports)
To investigate the impact of kelp and its bioactive component fucoidan as feed additives on lipid metabolism in large yellow croaker (Larimichthys crocea), an 8-week feeding experiment was conducted using diets supplemented with 3 % kelp (Saccharina japonica, KM group) and 0.2 % fucoidan (FM group). Lipidomic analysis identified over 700 distinct lipids in the muscle, categorized into five main categories and 36 lipid subclasses. Among these, triglycerides (TGs) and phosphatidylcholines (PCs) were the predominant lipid components, with levels in the KM group reduced to 66.34–87.65 % of control values, along with a specific 1.75-fold increase in lysophosphatidylethanolamine (LPE 16:0). Besides, most fatty acids (FAs) demonstrated decreased content in the KM group, except for specific increases in α-linolenic acid (C18:3n-3), arachidonic acid (C20:4n-6), eicosenoic acid (C20:1n-9) and eicosapentaenoic acid (C20:5n-3). The FM group showed both up- and down-regulated trends in lipid content with only a few polyunsaturated fatty acids (PUFAs) showing a decrease. Notably, both kelp and fucoidan supplementation modulated cholesterol metabolism, reducing total and low-density lipoprotein (LDL) cholesterols while increasing high-density lipoprotein (HDL) cholesterol. Moreover, gene expression analysis further supported this finding, showing significant down-regulation of fas, lpl, and srebp1 (genes related to FA synthesis) in two groups, while up-regulation of aco, pparα, and pgc-1α (genes promoting β-oxidation) in the KM or FM groups. These results demonstrated that kelp and fucoidan could effectively alter the lipid composition, supporting their potential as sustainable feed additives in aquaculture.